The Potential of Professional Learning Communities for Competence-Based Teaching in Tanzanian Secondary Schools - Mwakabenga, Rehema Japhet; Paine, Lynn (Papers in Education and Development, 2024)
Professional learning communities (PLCs) provide teachers with opportunities to learn from one another and enhance classroom practices. This qualitative study investigated the potential of PLCs in promoting competency-based teaching in Tanzanian secondary schools. The study employed a case study design involving interviews with 69 participants, including teachers, heads of schools, and students. Analysis indicated that teachers had not yet extracted the full potential of PLCs. PLCs reinforce examination-oriented teaching that encourages knowledge memorisation instead of maximising students ' active learning in challenging classroom environments. Among other recommendations, teachers should be trained on how to set up effective PLCs and manage them. Keywords: competence-based teaching; learner-centred teaching; communities of learning; teacher professional development